Predictors of stable coronary artery disease progression in the post-COVID period. - D. A. Derisheva; D. A. Yakhontov; V. L. Lukinov (Фундаментальная и клиническая медицина)
Aim. To evaluate the clinical course of stable coronary artery disease (CAD) depending on the timing of disease onset in relation to COVID-19 infection, and to identify predictors of disease progression during the post-COVID period. Materials and Methods. This study included 431 patients with stable CAD who had a confirmed history of COVID-19 between 2020 and 2023, with a minimum of 3 months between infection and enrollment. Patients were divided into two groups based on the timing of CAD diagnosis: patients diagnosed with CAD in the post-COVID period (n = 198, post-COVID-CAD) and patients diagnosed with CAD before their COVID-19 infection (n = 233, pre- COVID-CAD). We further evaluated clinical and laboratory parameters, including lipid profile (apolipoprotein A1, apolipoprotein B, lipoprotein( a)), N-terminal pro-brain natriuretic peptide (NT-proBNP), ST2, and coronary angiography. Logistic regression analysis was used to identify predictors of CAD progression. Results. Patients with pre- COVID-CAD were older (median age 62 vs. 61 years, p = 0.009), had a higher body mass index (BMI: 31.02 vs. 28.73 kg/m², p < 0.001), and a longer history of arterial hypertension (15 vs. 9.5 years, p < 0.001). COVID-19 was more severe in patients with pre-COVID-CAD, with a higher hospitalization rate (50.2% vs. 37.8%, p = 0.012) and more frequent moderate cases during the acute phase (58.7% vs. 45.9%, p < 0.009). Patients with pre-COVID-CAD also had a higher prevalence of prior myocardial infarction (51.0% vs. 26.7%, p < 0.001) and hemodynamically significant coronary artery lesions (86.2% vs. 67.6%, p < 0.001). Conversely, normal coronary arteries were more often observed in patients with post-COVID-CAD (8.5% vs. 7.2%, p = 0.003), possibly indicating microvascular involvement in post-COVID-CAD pathogenesis. Multifocal atherosclerosis was prevalent in both groups (75.7% vs. 79.8%, p = 0.351). Heart failure with mildly reduced ejection fraction (HFmrEF) was more common in patients with pre-COVID-CAD (10.7% vs. 5.0%, p = 0.034), whereas heart failure with preserved ejection fraction (HFpEF) predominated in patients with post-COVIDCAD (94.9% vs. 89.2%, p = 0.034). Left ventricular ejection fraction and glomerular filtration rate were significantly lower in patients with pre-COVID-CAD (60% vs. 62%, p = 0.007; 63.0 vs. 67.5 mL/min/1.73 m², p < 0.001, respectively). Laboratory indicators such as triglycerides, Lp(a), apoB, uric acid, and cystatin C were significantly elevated in patients with pre-COVID-CAD (p < 0.05). Multivariate analysis identified the following significant predictors of CAD progression in the post-COVID period: angina duration > 2.5 years, BMI > 29.66 kg/m², a history of moderate COVID-19, Lp(a) > 317.6 mg/dL, and NT-proBNP > 161.04 pg/mL. Conclusion. The timing of CAD onset in relation to COVID-19 significantly influences the disease course, emphasizing the need for a differentiated management strategy in post-COVID patients to predict CAD progression